FACTORS OF INFLUENCE STUDENTS' READING ABILITY (CASE STUDY AT SDN 105 PEKANBARU) - Ade Irma Suryani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Reading plays a crucial role in everyday life because it enables individuals to access the information they need. Students do not acquire reading skills by chance or through inspiration, but through systematic instruction. Reading is not an innate activity; it is a set of skills learned gradually and eventually mastered to become automatic. However, reading problems remain evident in primary schools, particularly the low reading proficiency of students in upper grades. This study was conducted due to the limited reading ability of fifth-grade students at SDN 105 Pekanbaru. Two students were selected as research subjects because their reading skills were significantly lower than those of their peers. To explore this issue, the researcher examined the factors influencing the students’ reading ability. This study employed a descriptive qualitative approach using surveys and observations. Data collection was carried out through interviews and documentation as supporting evidence. The findings obtained from triangulation of observations and interviews indicate that the factors influencing the reading ability of fifth-grade students at SDN 105 Pekanbaru include intellectual factors and psychological factors.